Endothelial nitric oxide synthase (eNOS) S1176 phosphorylation status governs atherosclerotic lesion formation - Nguyen, Tung D.; Rahman, Nur-Taz; Sessa, William C.; Lee, Monica Y. (Frontiers in Cardiovascular Medicine, 2023)
Objective We have previously demonstrated the in vivo importance of the Akt-eNOS substrate-kinase relationship, as defective postnatal angiogenesis characteristic of global Akt1-null mice is rescued when bred to ‘gain-of-function’ eNOS S1176D mutant mice. While multiple studies support the vascular protective role of endothelial NO generation, the causal role of Akt1-dependent eNOS S1176 phosphorylation during atherosclerotic plaque formation is not yet clear. Approach and results We herein bred congenic ‘loss-of-function’ eNOS S1176A and ‘gain-of-function’ eNOS S1176D mutant mice to the exacerbated atherogenic Akt1−/−; ApoE−/− double knockout mice to definitively test the importance of Akt-mediated eNOS S1176 phosphorylation during atherogenesis. We find that a single amino acid substitution at the eNOS S1176 phosphorylation site yields divergent effects on atherosclerotic plaque formation, as an eNOS phospho-mimic aspartate (D) substitution at S1176 leads to favorable lipid profiles and decreased indices of atherosclerosis, even when on a proatherogenic Akt1 global deletion background. Conversely, mice harboring an unphosphorylatable mutation to alanine (S1176A) result in increased plasma lipids, increased lesion formation and cellular apoptosis, phenocopying the physiological consequence of eNOS deletion and/or impaired enzyme function. Furthermore, gene expression analyses of whole aortas indicate a combinatorial detriment from NO deficiency and Western Diet challenge, as ‘loss-of-function’ eNOS S1176A mice on a Western Diet present a unique expression pattern indicative of augmented T-cell activity when compared to eNOS S1176D mice. Conclusions By using genetic epistasis approaches, we conclusively demonstrate that Akt-mediated eNOS S1176 phosphorylation and subsequent eNOS activation remains to be the most physiologically relevant method of NO production to promote athero-protective effects.